Plasma Prolactin and Progesterone Levels and the Risk of Gestational Diabetes: A Prospective and Longitudinal Study in a Multiracial Cohort - Li, Mengying; Song, Yiqing; Rawal, Shristi; Hinkle, Stefanie N.; Zhu, Yeyi; Tekola-Ayele, Fasil; Ferrara, Assiamira; Tsai, Michael Y.; Zhang, Cuilin (Frontiers in Endocrinology, 2020)
Objective: Prolactin and progesterone are implicated in glucose homeostasis in and outside of pregnancy. However, their associations with gestational diabetes (GDM) risk were not well understood. This study investigates this question in a prospective and longitudinal cohort. Methods: This is a nested case-control study of 107 incident GDM cases and 214 matched non-GDM controls within the NICHD Fetal Growth Studies-Singleton Cohort. Blood samples were collected at gestational weeks 10-14, 15-26, 23-31 and 33-39. The odds ratios (OR) of GDM were estimated using conditional logistic regression. The longitudinal changes in prolactin and progesterone were estimated using linear mixed-effects models. Results: Compared to controls, cases have significantly higher prolactin levels at weeks 10-14 (median: 50.4 vs. 42.1 ng/mL), and significantly lower progesterone levels at weeks 10-14 (median: 109.4 vs. 126.5 nmol/L). Prolactin levels at weeks 10-14 were significantly and positively associated with GDM risk; the adjusted ORs across increasing quartiles were 1.00, 1.13, 1.80, 2.33 (p-trend = 0.02). A similar but slightly attenuated association was observed at weeks 15-26 (p-trend = 0.05). Progesterone was not associated with GDM risk at either time points. Longitudinal changes in prolactin and progesterone between the first two visits were not associated with GDM risk. In addition, prolactin was significantly and positively associated with insulin and C-peptide levels at weeks 10-14, and significantly and inversely associated with C-peptide levels at weeks 15-26; progesterone was significantly and inversely associated with glucose and insulin levels. Conclusions: This study provided the first prospective evidence of a positive association between prolactin levels in early pregnancy and GDM risk.